Percutaneous transjugular coil embolisation (PTCE) method for closure of intrahepatic portosystemic shunts (IHPSS). Issue 9 (November 2013) - Wray, Jon
<x xml:space="preserve">Abstract</x> Surgical closure of an intrahepatic portosystemic shunt (IHPSS) was described in the previous issue of Companion Animal. Interventional radiology, the use of fluoroscopicallyguided catheter‐based techniques, has also been recently employed to successfully treat IHPSS in dogs. This case description introduces the method and results of interventional radiology closure of an intrahepatic shunt using the PTCE method.